European Level Collective Bargaining: A New Phase? - Grahl, John; Teague, Paul (Relations industrielles / Industrial Relations, 1991)
After nearly 2 decades on the side lines, European level collective bargaining is back on the industrial relations agenda. To a large extent, the resurgence of this notion can be attributed to the impact of the European Community's (EC) 1992 integration program on European economic and political life. For all the activity going on, it appears unlikely that EC-wide collective bargaining will come to play a significant role in industrial relations in the near future. There are 2 main dimensions to European collective bargaining: 1. the vertical dimension, which covers attempts to get greater collaboration and dialogue between trade unions and employers inside the institutional framework of the EC, and 2. the horizontal dimension, which includes developments at the enterprise and market levels aimed at promoting trade union or employer contact outside the confines of the nation state. If market completion leads to new regulatory arrangements within the EC, the social partners may be obliged to engage in meaningful discussion about collective bargaining.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Collective bargaining; Labor Unions; Labor negotiations; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Unions